Emergence of Kaposi's Sarcoma Herpesvirus-Associated Complications Following Corticosteroid Use in TB-IRIS. (12th October 2018) - Manion, Maura; Uldrick, Thomas; Polizzotto, Mark N; Sheikh, Virginia; Roby, Gregg; Lurain, Kathryn; Metzger, Dorinda; Mican, JoAnn M; Pau, Alice; Lisco, Andrea; Laidlaw, Elizabeth; Hammoud, Dima A; et al.
Abstract: Corticosteroid use was associated with development of Kaposi's sarcoma or multicentric Castleman disease in 3 patients with mycobacterial immune reconstitution inflammatory syndrome (IRIS) treated with corticosteroids. Monitoring for development of Kaposi's sarcoma and alternative treatment may be beneficial for patients with IRIS, especially in the presence of preexisting co-infection with Kaposi's sarcoma–associated herpesvirus.